KEAWETAN PAPAN PARTIKEL DARI BATANG SORGUM DAN KAYU AKASIA DENGAN PEREKAT UREA FORMALDEHIDA TERHADAP SERANGAN RAYAP TANAH - Viviana, Maya; Tavita, Gusti Eva (Universitas Tanjungpura, 2019)
High demand for timber is not balanced with the availability of wood, so that wood products need to be diversified, one of diversified is particleboard. Particleboards that have good physical and mechanical properties do not guarantee have good resistance to termite attacks. Research aimed to determine the durability of particleboards, interaction between adhesive concentration and composition of materials, and the optimum of adhesive concentration and composition of materials that are resistant to termites attacks. This research used a factorial RAL pattern experimental design with two factors. First factor is an adhesive concentration (8%, 10%, 12%) and second factor is a composition materials of sorghum : acacia wood (100%:0%, 50%:50%, 0%:100%), where each treatment is repeated three replications. 2cm x 2cm x 1cm of particleboards put into plastic glass containing 55 termites (50 workers and 5 soldiers). Observed period is 21 days. The parameters observed were the weight loss of particleboard and mortality of termites. Based on the classification of particle board resistance, the results showed that particle board generally has a medium to very resistance, except for 8% adhesive concentration with composition 100%:0% that categorize class IV durability with the highest weight loss value. Particle board with 10% adhesive concentration and the composition materials of 50% sorghum stalk : 50% acacia wood is categorize in class II durability is a capable treatment to resist termites attacks.Keywords: acacia wood, baggase sorghum, Coptotermes curvignathus, durability, particleboard